The Effect of Health Education Using Video Media on Knowledge About Bullying in Class VII Students of SMPN 1 Dungaliyo - Wiwi Susanti Piola; Leni Ali; Muriyati Rokani (PSPP JOURNALS, 2022)
Bullying is an act or behavior in which a child abuses power, both physically and verbally. Bullying behavior has a negative impact on children if it is not treated immediately. The purpose of this study was to determine the effect of health education education using video media on knowledge about bullying in seventh grade students of SMPN 1 Dungaliyo. Pre-experimental research design, population 125 students of class VII SMPN 1 Dungaliyo. The sample is 31 students of Class VII SMPN 1 Dungaliyo. Using the Cluster Random Sampling technique. The instrument used is a Test (Pre test and Post Test) and uses univariate analysis and bivariate analysis. The results obtained are that there is a significant effect of Health Education Using Video Media on Knowledge About Bullying in Class VII Students of SMPN 1 Dungaliyo.